Face detection with multiple cameras - Lui, Quan Fu. (2010)
This project shows the development of a framework that serves the purpose of video surveillance using computer. As security is becoming more important in organisations, the need for video surveillance will be highly favourable. With the invention of new technology and algorithm, it is very possible that complex system such as a fully automated video surveillance can be achieved.